The restorative effects of mosques: current knowledge, conceptual framework, and implications for environmental psychology - Mohd Mahudin, Nor Diana (IIUM Press, 2021)
The concept of restorative experiences, although originating from early theories of attention and neurological studies of mental functioning, has long been a central part of environmental psychology studies (Kaplan, 1995; Packer, 2014). In general, the concept argues that exposure to a restorative environment helps restore attention capacity, recover from mental fatigue, improve mood, and reduce stress (Hartig, 2004; Hartig, Kaiser, & Bowler, 2001). All of which are necessary psychological resources to sustain homeostatic balance, health, and well-being. Restorative experiences, thus, are regarded as important means of reducing mental fatigue, helping to balance competing demands of everyday life (Kaplan 1992), and contributing to the well-being and satisfaction of those who engage in them (Packer, 2014).